HARMONISA AKIBAT VARIABLE SPEED DRIVE LIFT - Redaksi Tim Jurnal (Energi & Kelistrikan, 2015)
Power quality problems are increasing and becoming a concern because of the use of power semiconductors in the industry and the loads that are used are very sensitive to variations. Non-linear loads in a three-phase four-wire system, three-wire systems has generally a large capacity such as for variable speed drive control in a elevator. Generally the use of variable speed drives on a elevator cause harmonic currents dominated by the fifth and seventh order harmonics currents. In this thesis, the measurement of harmonics due to variable speed drives on an elevator and will be concluded by extrapolation.